"(x^2D^2-xD+4)y=cos(logx)\\\\\n\\text{By euler equation.}\\\\\n(D'(D'-1)-D'+4)y=cosz\\\\\n(D'^2-2D'+4)y=cosz\\\\\n\\text{homogeneous differential equation is given by}\\\\\n(D'^2-2D'+4)y=0\\\\\n\\text{Auxiliary equation,}\\\\\nm^2-m+4=0\\\\\nm=1\\pm\\sqrt3i\\\\\n\\text{Therefore, general solution of homogeneous differential equationis}\\\\y=e^z(c_1cos(\\sqrt3z)+c_2sin(\\sqrt3z))\\\\\ny=x(c_1cos(\\sqrt3logx)+c_2sin(\\sqrt3logx))\\\\\n\\text{Now,finding the particular solution }\\\\\ny_p=\\frac{1}{(D'^2-2D'+4)}cosz\\\\\n=\\frac{1}{(-(1)^2-2D'+4)}cosz\\\\\n=\\frac{1}{(3-2D')}cosz\\\\\n=\\frac{3+2D'}{(9-4D'^2)}cosz\\space (\\text{Rationalise})\\\\\n=\\frac{3+2D'}{(9-4(-(1)^2)}cosz\\\\\n=\\frac{3+2D'}{13}cosz\\\\\n=\\frac{1}{13}(3cosz-2sinz)\\\\\n=\\frac{1}{13}(3cos(logx)-2sin(logx))\\\\\n\\text{Therefore, general solution of the given differential equation is}\\\\\ny=x(c_1cos(\\sqrt3logx)+c_2sin(\\sqrt3logx))+\\frac{1}{13}(3cos(logx)-2sin(logx))"
Comments
Leave a comment